Sports Augmented Cognitive Benefits: An fMRI Study of Executive Function with Go/NoGo Task - Qingguo Ding; Lina Huang; Jie Chen; Farzaneh Dehghani; Juan Du; Yingli Li; Qin Li; Hongqiang Zhang; Zhen Qian; Wenbin Shen; Xiaowei Yin; Pei Liang (Neural Plasticity)
Exercise is believed to have significant cognitive benefits. Although an array of experimental paradigms have been employed to test the cognitive effects on exercising individuals, the mechanism as to how exercise induces cognitive benefits in the brain remains unclear. This study explores the effect of dynamic neural network processing with the classic Go/NoGo task with regular exercisers. We used functional magnetic resonance imaging to analyze the brain activation of areas involved in executive function, especially inhibitory control. Nineteen regular joggers and twenty-one subjects as a control group performed the task, and their brain imaging data were analyzed. The results showed that at the attentive visual period, the frontal and parietal areas, including the prefrontal cortex, putamen, thalamus, lingual, fusiform, and caudate, were significantly enhanced in positive activities than the control group. On the other hand, in the following inhibitory control processing period, almost the same areas of the brains of the exercise group have shown stronger negative activation in comparison to the control group. Such dynamic temporal response patterns indicate that sports augment cognitive benefits; i.e., regular jogging increases the brain’s visual attention and inhibitory control capacities.